2008
DOI: 10.1002/jlcr.1543
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the radioastatination of a monoclonal antibody with astatine‐211 purified by wet extraction

Abstract: Astatine-211, a most promising α-particle emitter for targeted radiotherapy, is generally obtained by high-temperature distillation. However, a liquid-liquid extraction procedure (wet extraction) has also been described. The purpose of this study was to develop and optimize the labelling of the stannylated-activated ester N-hydroxysuccinimidyl-meta-trimethylstannylbenzoate ester (MeSTB) with astatine-211 extracted in di-isopropylether (DIPE) in the presence of the oxidant N-chlorosuccinimide (NCS). The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…In 1973, Neirincks and Smit reported extracting 211 At into DIPE, but used aqueous hydroxylamine to back-extract [31]. More recently Yordanov et al described a similar approach using DIPE or butylether for the extraction of 211 At [32], and Bourgeois et al described an approach using the DIPE extract directly for radiolabeling of m-Me 3 Snbenzoate N-hydroxysuccinimidyl ester [46]. Zona et al also described a similar wet chemistry approach to obtain 211 At on silver foils [33].…”
Section: Discussionmentioning
confidence: 99%
“…In 1973, Neirincks and Smit reported extracting 211 At into DIPE, but used aqueous hydroxylamine to back-extract [31]. More recently Yordanov et al described a similar approach using DIPE or butylether for the extraction of 211 At [32], and Bourgeois et al described an approach using the DIPE extract directly for radiolabeling of m-Me 3 Snbenzoate N-hydroxysuccinimidyl ester [46]. Zona et al also described a similar wet chemistry approach to obtain 211 At on silver foils [33].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it has been demonstrated that biomolecules can be radiolabeled efficiently using standard procedures with 211 At recovered with this method. 16 Chemical Properties of Astatine Despite more than 70 years of research on astatine, its chemistry is still not clearly established. The main reason is the fact that no stable isotope exists, the most stable isotope being 210 At with a half-life of only 8.1 hours.…”
Section: Purificationmentioning
confidence: 99%
“…In this technique, the irradiated bismuth target was dissolved in nitric acid, and the 211 At extracted by di-isopropylether (DIPE) instead of being distilled into a solution. The N-hydroxysuccinimidyl-meta-trimethylstannylbenzoate ester (MeSTB) has been used for radiolabeling with 211 At obtained by wet extraction methods [43,59].…”
Section: Atmentioning
confidence: 99%